Molecular epidemiology of Coxsackievirus A6 in Sarawak, Malaysian Borneo, from 2000 to 2015 - Sipol, S.I.; Saiful Ikhwan, Dayana; Wong, S.C.; Ooi, M.H.; Perera, David (Elsevier Inc., 2020)
Hand, foot and mouth disease (HFMD) affects mostly children with millions of infections notified every year particularly in Asia. In the last decade, Coxsackievirus A6 (CVA-6) has emerged as an important pathogen in HFMD epidemics replacing CVA-16 as a predominant serotype associated with uncomplicated HFMD. In Sarawak, CVA-6 has been detected since 2000. However a comprehensive study on the circulation of this virus has not been carried out to date. In this study, we investigated the molecular epidemiology of CVA-6 in Sarawak from 2000 to 2015 associated with HFMD.